Renewable Energy System Optimization: Mppt Inverter Integration, Energy Storage Systems, And Its Impact on Sustainability and Efficiency Use Of Energy - Ary Pratama Paluga; Anggara Trisna Nugraha; Rama Arya Sobhita; Mukhammad Jamaludin (P3M Politeknik Perkapalan Negeri Surabaya, 2024)
Abstract: This study endeavors to enhance the utilization of solar panel energy by employing MPPT inverters and integrating energy storage systems. It will be conducted at the Renewable Energy Laboratory, Institute of Technology Sampling, spanning one academic year. Following an experimental research format with a single control group, measurements will be taken pre and post integration of MPPT inverters and energy storage systems to assess energy efficiency and supply stability. Primary data will be gathered from direct measurements of solar panels with integrated MPPT inverters and energy storage systems, encompassing energy production, supply fluctuations, and system stability. Data collection methods include direct measurements with state-of-the-art energy measurement equipment and interviews with renewable energy experts and technicians. Control of variables such as weather conditions and energy consumption will ensure information validity, while external validity will be bolstered by comparing findings with existing literature. Statistical analysis using advanced software will identify significant differences pre and post integration. Additionally, qualitative observations will be conducted to evaluate system stability and the impact of optimization on the sustainability and efficiency of renewable energy utilization.